2013
DOI: 10.1158/1078-0432.ccr-12-3212
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Protein NEDDylation with MLN4924 Is a Novel Strategy to Target Cisplatin Resistance in Ovarian Cancer

Abstract: Purpose: Ovarian cancer has the highest mortality rate of all female reproductive malignancies. Drug resistance is a major cause of treatment failure and novel therapeutic strategies are urgently needed. MLN4924 is a NEDDylation inhibitor currently under investigation in multiple phase I studies. We investigated its anticancer activity in cisplatin-sensitive and -resistant ovarian cancer models.Experimental Design: Cellular sensitivity to MLN4924/cisplatin was determined by measuring viability, clonogenic surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 41 publications
6
90
1
Order By: Relevance
“…Accumulation of cell cycle regulatory proteins upon MLN4924 treatment was constantly accompanied with DNA damage response, which was partially responsible for the apoptosis and senescence induced upon NEDDylation inhibition (Soucy et al 2009a, b;Mackintosh et al 2013;Jia et al 2011a, b). Given the potency and the unique mechanism of MLN4924 in inducing DNA damage in cancer cells, synergistic interactions between MLN4924 with other DNA-damage-inducing compounds (platinum, cytarabine, Cisplatin, mitomycin C) and radiation will promote its incorporation into current treatment regimens for human malignancies (Nawrocki et al 2013(Nawrocki et al , 2015Yang et al 2012;Wei et al 2012;Kee et al 2012;Jazaeri et al 2013;Garcia et al 2014). These studies highlighted potential incorporation of MLN4924 into current treatment regimens as addition of MLN4924 was shown to sensitize malignant cells to those traditional therapeutic strategies.…”
Section: Skp2mentioning
confidence: 99%
“…Accumulation of cell cycle regulatory proteins upon MLN4924 treatment was constantly accompanied with DNA damage response, which was partially responsible for the apoptosis and senescence induced upon NEDDylation inhibition (Soucy et al 2009a, b;Mackintosh et al 2013;Jia et al 2011a, b). Given the potency and the unique mechanism of MLN4924 in inducing DNA damage in cancer cells, synergistic interactions between MLN4924 with other DNA-damage-inducing compounds (platinum, cytarabine, Cisplatin, mitomycin C) and radiation will promote its incorporation into current treatment regimens for human malignancies (Nawrocki et al 2013(Nawrocki et al , 2015Yang et al 2012;Wei et al 2012;Kee et al 2012;Jazaeri et al 2013;Garcia et al 2014). These studies highlighted potential incorporation of MLN4924 into current treatment regimens as addition of MLN4924 was shown to sensitize malignant cells to those traditional therapeutic strategies.…”
Section: Skp2mentioning
confidence: 99%
“…Targeting neddylation pathway has been recently demonstrated as an attractive anticancer strategy, evidenced by the efficacy of the NAE inhibitor MLN4924, a first-in-class anticancer agent, in a multitude of preclinical studies (1)(2)(3)(11)(12)(13)(14)(15)(16)(17)(18)(19). Currently, MLN4924, used as a single agent or in combination with traditional chemotherapeutics, is under investigation in quite a few of phase I/II clinical trials (http://www.clinicaltrials.gov) and has exhibited promising clinical activity in both advanced solid tumors and relapsed/refractory multiple myeloma or lymphoma (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have established that targeting NAE with MLN4924 effectively overcomes platinum resistance in preclinical models of ovarian cancer (15,16). Additionally, a synergic cytotoxic effect between cisplatin and MLN4924 was observed in platinum-sensitive and -resistant ovarian cancer cells (15,16).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, MLN4924 exhibits potent antitumor activity in numerous types of cancer (14). Notably, previous studies have indicated that MLN4924 overcomes platinum resistance in preclinical models of ovarian cancer (15,16), suggesting that inhibiting neddylation with MLN4924 may be a novel strategy to target drug resistance in cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation